جودة التعليم في الجامعة اللبنانية الفرنسية – الواقع والطموح - ا.د. شالل حبيب الجبوري (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
As we know the quality of education in any university is the responsibility of the university its self, so for the purpose of this research will trying to fix clear structure for the system of quality by determining the main variables of quality system with practical suggestion to help the decision maker in the university to take the appropriate decision will strengthen the quality system. In order to reach the main object of this research we create questionnaire to ask the university teachers which include the main variables that related to quality of education as follow; -Mission and Vision of the university. -The staff (teachers) -The Students -Services. -Scholastic programs. -The financial &physical sides(aspects). -Scientific research . Then after analyzing the collected data we get the following: 1- a-At the level of the results there is some negative points in the university needs to avoid them. b-According to the opinion of teachers the following variables have the highest percentage among the seven axes. -Mission &Vision 16% -Students 15.6% -Services 14.1% -Scientific research 13.7% 2-At the level of conclusions we notes the following: First: There is some teachers are not realizing the main variables that related to quality. Second: Absence of some important variables that related to quality from quality sys tem of the university. Third: Does not exist system for collecting data which can used to get a clear indicators for quality.